Elucidation of ultrasonic wave-assisted electrodeposited AgPd nanoalloy from ionic liquid as an efficient bifunctional electrocatalyst for methanol oxidation and hydrogen peroxide reduction. (10th November 2019) - Sriram, P.; Kumar, M. Kaleesh; Selvi, G. Thamarai; Jha, Niki S.; Mohanapriya, N.; Jha, Shailendra K.
Abstract: A combined ultrasonic wave-assisted electrodeposition approach has been elucidated for the preparation of AgPd nanoalloy catalyst films on glassy carbon plate from an ionic liquid medium, and explored as a bifunctional electrocatalyst. The synergetic effects of variable frequency ultrasonic-wave and electrodeposition process and related parameters have been analyzed to understand the enhanced electrocatalytic activity towards small molecules, such as methanol electro-oxidation and hydrogen peroxide (H2 O2 ) electro-reduction in an alkaline medium. The characterization techniques like field emission scanning electron microscopy (FE-SEM), atomic force microscopy (AFM), high resolution transmission electron microscopy (HR-TEM), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), energy dispersive X-ray fluorescence spectroscopy (ED-XRF) and electrochemical techniques like cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were employed to verify the alloy nature of the as-deposited AgPd nanostructure catalysts. Further, the scope of application to construct the nonenzymatic electrochemical sensor for H2 O2 with as-prepared nanoalloy electrocatalysts has been also tested. Moreover, among the as-prepared catalysts, the AgPd-USD-45 catalyst exhibits better catalytic activity for both the reactions, suggesting the potential for further development of high performance non-Pt catalysts based alkaline fuel cells and nonenzymatic electrochemical sensor.